2015
DOI: 10.1002/j.1556-6978.2015.00068.x
|View full text |Cite
|
Sign up to set email alerts
|

The Flipped Classroom in Counselor Education

Abstract: The flipped classroom is proposed as an effective instructional approach in counselor education. An overview of the flipped-classroom approach, including advantages and disadvantages, is provided. A case example illustrates how the flipped classroom can be applied in counselor education. Recommendations for implementing or researching flipped classrooms are shared.Keywords: flipped classroom, pedagogy, counselor education Although the concept of the flipped classroom has been around for years and in various fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(78 citation statements)
references
References 10 publications
3
66
0
7
Order By: Relevance
“…For example, 12 of 15 students reported that reviewing narrated PowerPoints before class facilitated their learning "somewhat" or "very much." Similarly, 12 students reported that participating in small group experiential projects in class "very much" facilitated their learning (Moran & Milsom, 2015). This case study demonstrates the relevance and feasibility of using a flipped learning approach in counselor education.…”
Section: Research On Flipped Learningmentioning
confidence: 80%
See 2 more Smart Citations
“…For example, 12 of 15 students reported that reviewing narrated PowerPoints before class facilitated their learning "somewhat" or "very much." Similarly, 12 students reported that participating in small group experiential projects in class "very much" facilitated their learning (Moran & Milsom, 2015). This case study demonstrates the relevance and feasibility of using a flipped learning approach in counselor education.…”
Section: Research On Flipped Learningmentioning
confidence: 80%
“…Much of the current interest in flipped learning can be traced to high school science teachers Jonathan Bergmann and Aaron Sams, who began flipping their classes in 2006 and have since published their experiences (Bergmann & Sams, 2012;Moran & Milsom, 2015). Their original model of flipped learning is referred to as the Traditional Flipped Learning Model, and includes previously described components such as students watching prerecorded video lectures outside of class and engaging in application-based activities in class.…”
Section: Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…And, while he says, it takes a little while for students to get used to the system, as the year progresses he sees them asking better questions and thinking more deeply about the content. After flipping his classroom, Bergmann says he can more easily query individual students, probe for misconceptions around scientific concepts, and clear up incorrect notions [2]. The flip's focus is to highlight the self-study in advance of the class and the strengthen counseling on classroom, which achieves the transfer of learning "main front", so that students can search for knowledge independently in a relaxed and free environment.…”
Section: Flipped Classroommentioning
confidence: 99%
“…Hutchings and Quinney (2015) conducted a study still conducted lectures in class. Moran and Milsom (2015) used narrated PowerPoint presentations outside of class. They still required a great deal of application level work to be conducted outside of class time that work was often used to create, "minilectures to address any content areas for which a large percentage of students expressed or demonstrated confusion or that the instructor wanted to highlight during class" (Moran & Milsom, 2015, pp 36-7).…”
Section: Post-secondary Flipped Researchmentioning
confidence: 99%